1988
DOI: 10.1128/iai.56.3.665-672.1988
|View full text |Cite
|
Sign up to set email alerts
|

Serial isolates of Pseudomonas aeruginosa from a cystic fibrosis patient have identical pilin sequences

Abstract: Five isolates of Pseudomonas aeruginosa (CD2, CD3, CD4, CD5, and CD10) from a patient with cystic fibrosis were examined with regard to several genotypic and phenotypic characteristics to determine whether the patient was colonized with one or several distinct strains. Isolates CD2, CD3, and CD4 were obtained from a single sputum sample, and CD5 and CD10 were obtained 1 and 2 years later, respectively. On the basis of colonial morphology, serotyping, and antibiograms, the five isolates appeared to be different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…Most recent research suggests that, once one strain colonizes the lung of the CF patient, this strain remains the dominant strain within the lung, and changes in the strain type are very rare (8,12,14,23,28). The results we obtained support this.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent research suggests that, once one strain colonizes the lung of the CF patient, this strain remains the dominant strain within the lung, and changes in the strain type are very rare (8,12,14,23,28). The results we obtained support this.…”
Section: Discussionmentioning
confidence: 99%
“…Most of such strains are sensitive to the bactericidal effect of normal human serum and are nontypeable, autoagglutinable, or agglutinable by multiple typing sera (9,10,26,27). Moreover, we and others (19, 21) have demonstrated that isolates with different LPS serotypes often prove to be clonally related when examined by gene probing and restriction fragment length polymorphism (RFLP) techniques. Therefore, conventional serotyping methods do not offer the discriminatory power necessary to distinguish among isolates and provide answers to basic epidemiological questions.…”
mentioning
confidence: 99%
“…The polysaccharides used are all clinically relevant antigens. P. aeruginosa is an important cause of infection in cystic fibrosis and burn patients (24,26), S. mutans is strongly implicated in the development of dental caries (20), Neisseria meningitidis causes meningitis primarily in children (27), and S. pneumoniae causes middle ear infection in children and pneumonia in the elderly (23). Our present studies show, for instance, that the antibody response to SM can be significantly enhanced by increasing Ta-cell activity.…”
Section: Discussionmentioning
confidence: 51%